Ranolazine Provides Benefit over Placebo for T2DM Patients with Angina - Hand, Larry (MD Conference Express, 2013)
In a trial focused on the treatment of stable angina in patients with type 2 diabetes, ranolazine significantly reduced the frequency of angina episodes compared with placebo. This article presents the results of the Type 2 Diabetes Evaluation of Ranolazine in Subjects With Chronic Stable Angina study [TERISA; Kosiborod M et al. J Am Coll Cardiol 2013].